Aquinas, Darwin and Natural Law: Teleology and Immutability of Species - Pienaar, Sebastiana (New blackfriars, 2021)
Natural Law theory is the theory that nature has built within it a set of objective norms or laws which are universally applicable and can be discovered by reason. It is derived from nature rather than from the rules of society in determining an objectivist moral theory. It has a long history of tradition beginning with the ancient Greeks and Romans up to the present day. The purpose of this essay is to argue Darwin's theory of natural law can be accommodated by Aquinas’ theory of natural law. The secondary literature of both figures is vast and changing, but this essay will mostly be restricted to looking at their primary texts on the topic. From this, it will be evident they shared many thoughts in common – the primary one being that morality begins with biology. There are objections to the compatibility of their theories, but space restricts me to addressing only two of them: teleology and immutability of species.